Google Traffic sebagai Masukan Kebijakan Transportasi Perkotaan (Studi Kasus: Kota Bandar Lampung) - Muhammad Zainal Ibad; Rahayu Sulistyorini; Chania Rahmah (Diponegoro University, 2020)
Congestion in urban areas is vulnerable because of the impact of the growth of activities and an increasingly specialized and complex economy. For this reason, it is necessary to formulate a good urban transportation policy to accommodate increased urban transportation needs. Google Traffic is a feature found on Google Maps to see the level of congestion in an area. Google Traffic can detect an area with red, yellow or green indications through the principle of Real Time Data using data from the Global Positioning System (GPS). This study wanted to see how the use of the Google Traffic Feature as input to urban transportation policies by looking at existing urban transportation policies, analyzing the movement system model on Google Traffic, and analyzing the development of Google Traffic model policies, which would be useful for the development of Urban Transportation Policies, especially Bandar Lampung City as a case study.